Developing Adaptive ASN Leadership in the Society 5.0 Era: An Integrated Conceptual Framework for Education and Training - Muhammad Taufiq; Ade Suhendar (International Journal on Education Issues, 2026)
Purpose - This study aims to formulate strategic education and training models to prepare Civil Servant (ASN) leadership in the era of Society 5.0, addressing a critical gap in the literature regarding the integration of digital transformation, merit systems, and leadership development in public sector governance. The research seeks to generate conceptual insights into how leadership competencies can be systematically developed to respond to VUCA dynamics and the increasing demand for adaptive, technology-enabled public administration. Design/Methodology/Approach - The study employs a qualitative approach using a descriptive-analytical literature review. Data were collected through systematic identification, screening, and selection of relevant academic publications focusing on digital leadership, adaptive governance, merit systems, and public sector training models. The analysis was conducted using a systematic literature review framework complemented by thematic synthesis and systematic mapping to construct a layered conceptual framework model for ASN leadership development. Findings - The findings reveal that ASN leadership in the Society 5.0 era must be characterized by digital leadership capability, adaptive and transformational capacity, collaborative governance orientation, and agile bureaucratic behavior. The study further identifies that effective education and training strategies should integrate digital-based training systems, HRIS-based needs assessment, blended learning models, and talent management aligned with merit principles. The proposed conceptual framework model demonstrates that leadership development must be designed as an integrated and dynamic ecosystem linking strategic context, training processes, competency outputs, and institutional transformation outcomes. Originality/Value - This research offers a novel conceptual framework for ASN leadership development by integrating digital transformation, adaptive leadership theory, and public sector training strategy within the context of Society 5.0. The study contributes theoretically to the discourse on public administration reform and practically provides strategic guidance for policymakers and training institutions in redesigning ASN education and leadership development programs to support sustainable bureaucratic transformation.